Analysis of the interferon-γ-induced secretome of intestinal endothelial cells: putative impact on epithelial barrier dysfunction in IBD - Naschberger, Elisabeth; Flierl, Christian; Huang, Jinghao; Erkert, Lena; Gamez-Belmonte, Reyes; Gonzalez-Acera, Miguel; Bober, Magdalena; Mehnert, Martin; Becker, Christoph; Schellerer, Vera S.; Britzen-Laurent, Nathalie; Stürzl, Michael (Frontiers in Cell and Developmental Biology, 2023)
The development of inflammatory bowel diseases (IBD) involves the breakdown of two barriers: the epithelial barrier and the gut vascular barrier (GVB). The destabilization of each barrier can promote initiation and progression of the disease. Interestingly, first evidence is available that both barriers are communicating through secreted factors that may accordingly serve as targets for therapeutic modulation of barrier functions. Interferon (IFN)- is among the major pathogenesis factors in IBD and can severely impair both barriers. In order to identify factors transmitting signals from the GVB to the epithelial cell barrier, we analyzed the secretome of IFN--treated human intestinal endothelial cells (HIEC). To this goal, HIEC were isolated in high purity from normal colon tissues. HIEC were either untreated or stimulated with IFN- (10 U/ml). After 48 hrs, conditioned media (CM) were harvested and subjected to comparative hyper reaction monitoring mass spectrometry (HRMTM MS). In total, 1084 human proteins were detected in the HIEC-CM. Among these, 43 proteins were present in significantly different concentrations between the CM of IFN-- and control-stimulated HIEC. Several of these proteins were also differentially expressed by various murine colitis models as compared to healthy animals supporting the relevance of these proteins secreted by inflammatory activated HIEC in the inter-barrier communication in IBD. The angiocrine pathogenic impact of these differentially secreted HIEC proteins on the epithelial cell barrier and their perspectives as targets to treat IBD by modulation of trans-barrier communication is discussed in detail.